Representasi Ageism dalam Film "The Intern" (2015) - Lidya Ernasari (Jurnal Ilmu Komunikasi, 2022)
Ageism is defined as discrimination shown to groups of elderly people. This research uses a qualitative method based on a critical discourse analysis approach to a movie that raises the theme of aging or aging entitled "The Intern '' (2015). Telling the story of the life of the elderly after their retirement, the film is interesting to study because of its sensitive position about aging, which according to some research, things related to aging are still portrayed with negative stereotypes in society. For this reason, this research aims to analyze the depiction of ageism in the film based on Teun A. Van Dijk's critical discourse, which is analyzed through several levels: macro structure, superstructure, and microstructure. The results obtained, the researcher states that the movie "The Intern" represents Ageism with a more positive image.